THE VIOLATION OF COOPERATIVE PRINCIPLES ON STUDENTS’ RESPONSES TOWARD TEACHER QUESTIONS IN TEFL CLASS - Sri Agung, Winantu Kurnianingtyas (IAIN PONOROGO, 2016)
Questioning is mostly conducted in learning process. As the reasons, by giving questions, teacher engages communicative interaction with students in classroom. But sometimes the communication can run effectively. The participants ordinary, broke the communication roles. This research investigates violation of maxims on students’ responses toward teacher question and determines the dominant type of maxim which is violated on students’ responses. This research was conducted qualitative research. And the research found that there were three types of maxim that were violated on students maxim of quantity, maxim of quality and maxim of manner. Then, maxim of quantity was mostly violated on students’ responses.